A New Way in New Year - Mohammadi Tofigh, Arash (Journal of Lasers in Medical Sciences, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has forced numerous changes in our lives. Many of us lost our loved ones in this tragedy. Serendipitously, there were some good changes for patients and surgeons too. For example, telemedicine has been extensively integrated into patient care visits for the benefit of both the patients and the care providers. In the Journal of Lasers in Medical Sciences (JLMS) , we are also undergoing a significant change. From now on, the publication routine of the journal changes from quarterly to continuous. This means that once an article is accepted for publication, there will be no need to wait for the next issue to be published, and the article will be displayed on the journal site immediately and indexed in global references. This significantly reduces the waiting time for authors to see the results of their work and efforts. As a result, one of the main concerns of the authors, which was the long queue for the publication of the accepted article, is resolved. Another point is that we intend to publish a volume of the journal every year without separate issues so the citation method to the articles will change a little. Over the past several years, JLMS has experienced a substantial increase in the number and quality of submissions and the depth and breadth of Laser science in these submissions. This welcome growth in volume and complexity, however, has challenged the review capacity of the co-editors and laid bare an insufficient organizational structure. We are extremely fortunate to have an excellent editorial board loaded with talented individuals with extensive expertise and a considerable depth of knowledge. Because of the riches of our editorial board, following a highly competitive search, we are introducing a new organizational structure that will include section editors. We are excited to introduce these new editors, who bring expertise, energy, and networks of respected, knowledgeable colleagues in their respective specialties to JLMS. We are grateful for their unwavering commitment to the peer review process that will help us to upgrade the level of our journal. Please join us, and feel free to share your thoughts with us! DOI:10.34172/jlms.2021.01